P0233ISOLATED MICROHEMATURIA IN ADOLESCENTS IS NOT ASSOCIATED WITH RENAL OR URINARY TRACT CANCER IN MIDDLE AGE. (6th June 2020) - Leiba, Adi; Fishman, Boris
Abstract: Background and Aims: Chronic or persistent isolated microhematuria (microhematuria without proteinuria) is not as benign as originally thought. It has been associated with an almost 20-fold risk of developing ESRD ( End Stage Renal Disease) in adulthood. It is still unclear if this chronic glomerular bleed increases the risk of renal or urinary tract tumors, secondary to ongoing irritation and inflammation. This is a valid question, especially as an adult with long standing isolated "glomerular" microhematuria can appear with an event of macrohematuria. In order to answer these questions, we studied the association between adolescent microhematuria and renal or urinary tract tumors in adulthood. Method: A retrospective study based on a cohort of 2, 172, 866 Jewish adolescents (60% men) aged 16-19 who underwent a mandatory physical examination between ages of 16 and 19 years from 1967 to 2007 prior to their conscription. Urothelial Transitional cell carcinoma (TCC) and Renal cell carcinoma (RCC) incidence through December 31, 2012 was identified by linkage to the national cancer registry. Multivariable-adjusted Cox regression models were used to estimate hazard ratios (HRs) for RCC and TCC among adolescents who were diagnosed with persistent asymptomatic isolated hematuria after comprehensive medical evaluation. The models were adjusted for: Sex, age, year of birth, socio-economic status, BMI, years of education and country of origin. Results: Over a median of 22 years (interquartile range of 13-31 years) of follow-up, 2007 and 1112 incident cases of TCC and RCC, respectively, occurred amongst the study population. Persistent hematuria was not associated with TCC with crude HR 1.15 (95% CI, 0.37-3.57) and adjusted HR of 1.08 (95% CI, 0.35-3.36), nor with RCC with crude HR 1.11 (95% CI, 0.28-4.457) and adjusted HR of 0.93 (95% CI, 0.23-3.75). Conclusion: Isolated persistent microhematuria, while carrying a small risk of kidney disease progression, is not associated with either renal or urinary tract tumors. Screening guidelines among these patients should follow the general age and sex- matched approach.